AAPS Open - Riley, Christopher M.
AAPS Open provides a global forum for the rapid and barrier-free publication of reports of original research that demonstrates applications of scientific concepts and techniques across the breadth of the pharmaceutical sciences. Fully peer-reviewed, AAPS Open supports the international community of experts in pharmaceutical sciences by providing a venue for articles that further the understanding of all aspects of the field. A high degree of innovation is not a required element for publication; the journal seeks to publish papers that are technically sound. AAPS Open welcomes reports from experimental or theoretical studies during the normal course of development of a drug candidate, e.g., assay development and validation, formulation, stability, metabolism screening, bioavailability assessment and comparison, food effects studies, manufacturing approaches, and so forth.